Comparison of force-based and displacement-based methods for seismic design of buildings - Varughese, Jiji Anna; Menon, Devdas; Prasad, A. Meher (Journal of Structural Engineering, 2024)
Displacement-based design (DBD) methods are emerging as the latest tools for performance-based seismic design and as a viable alternative to conventional force-based design method (FBD). FBD starts with an estimation of base shear force, which is calculated based on the fundamental period and ductility capacity of the structure. This base shear force is distributed to the various floor levels based on the fundamental mode shape, and the structure is designed for these lateral loads. Unlike FBD, DBD method requires explicit consideration of displacements. Typically, DBD determines a target displacement demand and then calculates the required base shear capacity to achieve this demand. In this method, the lateral loads at various floor levels are obtained based on an assumed inelastic displacement profile. This paper presents the findings of a study that uses the FBD method and DBD method to design a typical four-storeyed and a nine-storeyed regular frame. The performances of the frames were assessed using nonlinear time history analysis and their relative performances are reported.